Sistem Pengendalian Internal dan Penerapan Good University Governance terhadap Kualitas Laporan Keuangan pada Perguruan Tinggi Keagamaan Islam Negeri di Aceh - Ayumiati, Ayumiati; Jalilah , Jalilah (Jurnal Samudra Ekonomi dan Bisnis, 2023)
The credibility of a PTKIN financial report is very important, especially for stakeholder decision making to fund the sustainability of PTKIN in accordance with the planned targets. Among the indicators that affect the quality of financial reports are the internal control system and good university governance (GUG). The purpose of this study was to determine the application and influence of SPI and GUG on the quality of financial reports presented at PTKIN in Aceh. The approach in this study was descriptive quantitative by distributing questionnaires to the SPI and finance departments at the three PTKINs in Aceh. The results of this study indicate that there is a positive and significant effect of SPI and GUG on the quality of the financial reports presented by PTKIN.